Konsep Qiyas Dan Ad Dalil Dalam Istimbat Hukum Ibn Hazm - Haika, Ratu (FENOMENA, 2012)
Ibnu Hazm is a distinguished Moslem leader who really holds fast to the nash. That is why, he critics hard the other Moslem leaders who take the rationality role in establishing a regulation. In his point of view, Islamic law comes from Allah SWT which is clearly written in Al Qur’an and Sunnah, and implemented consensusily by all Moslems. Ijma’ basically should based on the the nash of Quran because there no ijma’ without following the nash. So that, Ibnu Hazm states that there are three sources of the law as main base of implementing the law. Ibnu Hazm refuses the qiyas as source of the law. In term of his refuse of the qiyas, Ibun Hazm promotes a new perspective in responding the comtemporer problems that they are not found in the nash explicitely. The thought was known as ad dalil.Then, the concept of ad dalil is considered as one of the sources of in the Islamic law that there is no different to the qiyas used by other Moslem leaders previously.